Analysis of the mean electrical axis of the heart from standard electrographic leads in normal adult males - Rajesh Prajapati; Neebha Amatya; Rajab Rana Magar; Ripti Shrestha; Prakash Baral; Narayan Mahotra (Journal of Karnali Academy of Health Sciences)
Background: Electrocardiogram has been widely applied as a diagnostic tool for cardiovascular disease. The concept of the cardiac vector is crucial for the clinical application in ECG interpretation.